Walking Pedagogy for Science Education and More-Than-Human Connection - Beavington, Lee (Journal of the Canadian Association for Curriculum Studies, 2021)
This literary-visual métissage weaves together stories, scholarship and photographs. What can be unearthed—science education, embodied knowledge, environmental ethics—when we walk on the land? Embodied and sensorial engagement fosters relational and enlivening educational experiences. Whether preschool or post-doc, direct sense experience offers not only active and experiential pedagogy, but also a spiritual attunement with the natural world. Now, amid the climate crisis and screen fatigue pandemic, such Earth resonance is of utmost import. Let us walk through a snowy forest, ponder what counsel our shoeless feet (and David Abram) afford us, and envision the learning environment as an emergent and adaptable opportunity for connection and wonder.